Chicago expressway system retrospective social benefits minus social costs analysis. Issue 2 (June 2021) - Arkell, Reginald
Highlights: Retrospective social benefit-cost analysis epitomized imprudence of city expressway system. Optimal road pricing/limiting expressways to exurbia more than doubled net welfare. Opportunity costs of reduced travel were large for collective transport outlays/damages. Dismissing the Theory of the Second Best is a burden to sustainability. Abstract: The rising demand for transportation and its impact on global warming is a critical societal problem. There is a dearth of ex post facto studies that comprehensively quantify the value of an urban expressway system and its contribution to this dilemma. This article addresses the void with a retrospective social benefits minus social costs analysis of the Chicago city expressway system (project). Monetized values were included for externalities not available to planners when the decision was made to build the highway network. The results of this analysis revealed that net present value (NPV) was clearly positive and substantial. The study also analyzed a hypothetical alternative scenario without the project. This approach assumed internalized regionwide road pricing to account for most known social costs and address the Theory of the Second Best issue. The results showed that NPV is about 3 times higher compared to the project. The project had considerable opportunity costs of lost reductions in travel demand, accidents, environmental impacts, and other transport externalities. Estimated total deadweight loss of the project was more than 10, 000 million (1960 ) over the period of 1947–1996 at a mid-range 5 percent discount rate. The outcome is highly dependent upon the assumed impact of optimal pricing on travel demand. Follow-up research is recommended to quantify impacts of comparable systemic roadway pricing under proposed scenarios of various highway capacities to assess impacts on welfare and carbon emissions.